Penerapan SPPKB Melalui Teknik NHT Dalam Pembelajaran Matematika - Indah Purnama Putri (Journal on Education, 2023)
In teaching mathematics, lecturers are not only required to be able to master the material being taught, but also must be able to present the subject matter in a systematic manner. One of the strategies that can be carried out by lecturers is implementing learning strategies to improve thinking skills (SPPKB) through techniques Numbered Heads Together (NHT) in learning mathematics. With SPPKB through NHT can increase the activity and learning outcomes of mathematics. The research data is the result of learning mathematics obtained from quizzes carried out 6 times. From the final test, it was obtained that the percentage of student learning completeness reached 70% with an average of 61.5. furthermore, to see student activities carried out observations. Observation data analysis was carried out using percentage techniques. Based on the results of observations at each meeting and each indicator, it can be seen the development of activities carries out by students during the learning process with SPPKB through the NHT technique.